Dairy Farming Development Strategy in Indonesia: Increasing Production and Welfare of Local Farmers - Agus Rohmat Hidayat (Politeknik Siber Cerdika Internasional, 2025)
Indonesia's national milk production only meets approximately 26% of domestic demand, leading to a dependency on imports and impacting the welfare of local dairy farmers. This phenomenon indicates weak institutional structures and suboptimal technology adoption in small-scale dairy farming systems. This study aims to analyze the current state of productivity and welfare of dairy farmers in Indonesia, identify challenges and opportunities for business development, and formulate development strategies based on institutions, technology, and policies. The research method used is a descriptive qualitative case study approach, supported by quantitative data (mixed methods). The study sample consisted of 100 farmers from five dairy cattle production centers, collected through questionnaires, interviews, field observations, and documentation. Data analysis techniques included descriptive analysis, SWOT analysis, and triangulation of data sources. The results show that participation in cooperatives, especially those partnering with industry, significantly increases milk production and farmer income. Farmers in cooperative partnerships produce an average of 14.5 liters per cow per day and earn Rp4.5 million per month, compared to non-cooperative farmers who only produce 10.5 liters and earn Rp2.1 million. Prominent weaknesses include low adoption of digital technology, limited access to capital, and unprofessional institutional capacity. The study’s conclusions emphasize that an effective dairy farming development strategy requires cross-sector integration, strengthening cooperatives, and technological and managerial transformation. Policy recommendations include implementing integrated models that promote digital technology adoption, cooperative reforms, and enhanced institutional capacity to foster a competitive and sustainable livestock system, ensuring broader welfare improvements for farmers.